Detection of blaCTX-M and blaDHA genes in stool samples of healthy people: comparison of culture- and shotgun metagenomic-based approaches - Campos-Madueno, Edgar I.; Aldeia, Claudia; Perreten, Vincent; Sendi, Parham; Moser, Aline I.; Endimiani, Andrea (Frontiers in microbiology, 2023)
We implemented culture- and shotgun metagenomic sequencing (SMS)-based methods to assess the gut colonization with extended-spectrum cephalosporin-resistant Enterobacterales (ESC-R- Ent ) in 42 volunteers. Both methods were performed using native and pre-enriched (broth supplemented with cefuroxime) stools. Native culture screening on CHROMID ® ESBL plates resulted in 17 positive samples, whereas the pre-enriched culture (gold-standard) identified 23 carriers. Overall, 26 ESC-R- Ent strains (24 Escherichia coli ) were identified: 25 CTX-M and 3 DHA-1 producers (2 co-producing CTX-Ms). Using the SMS on native stool (“native SMS”) with thresholds ≥60% for both identity and coverage, only 7 of the 23 pre-enriched culture-positive samples resulted positive for bla CTX-M / bla DHA genes (native SMS reads mapping to bla CTX-M / bla DHAs identified in gold-standard: sensitivity, 59.0%; specificity 100%). Moreover, an average of 31.5 and 24.6 antimicrobial resistance genes (ARGs) were detected in the 23 pre-enriched culture-positive and the 19 negative samples, respectively. When the pre-enriched SMS was implemented, more bla CTX-M / bla DHA genes were detected than in the native assay, including in stools that were pre-enriched culture-negative (pre-enriched SMS reads mapping to bla CTX-M / bla DHAs identified in gold-standard: sensitivity, 78.3%; specificity 75.0%). In addition, the pre-enriched SMS identified on average 38.6 ARGs/sample, whereas for the corresponding native SMS it was 29.4 ARGs/sample. Notably, stools resulting false-negative by using the native SMS had lower concentrations of ESC-R- Ent (average: ~10 5 vs. ~10 7 CFU/g) and E. coli classified reads (average: 193,959 vs. 1.45 million) than those of native SMS positive samples. Finally, the detection of bla CTX-M / bla DHA genes was compared with two well-established bioinformatic tools. In conclusion, only the pre-enriched SMS assured detection of most carriers of ESC-R- Ent . However, its performance was not comparable to the pre-enriched culture-based approach.